Modern Pedagogical Specific Aspects Of Development Of Suggestive Skills In Future Teachers - Yuldashev Elyorjon Sodiqovich (Euro Asian Journal Publishing, 2024)
In this article, there is a classification of pedagogical skills and the socio-pedagogical necessity of their development in teachers, improving the system of training pedagogues today, improving the skills of pedagogues, developing pedagogical skills and abilities. Each pedagogical ability has its own characteristics, and it is explained that it is necessary for a pedagogue to know them and to be able to develop these abilities.
Keywords: sports; folk traditional values; intercultural relations